Numerical Solution of the Absolute Value Equations Using Two Matrix Splitting Fixed Point Iteration Methods - Rashid Ali; Asad Ali; Mohammad Mahtab Alam; Abdullah Mohamed (Journal of Function Spaces)
The absolute value equations (AVEs) are significant nonlinear and non-differentiable problems that arise in the optimization community. In this article, we provide two new iteration methods for determining AVEs. These two approaches are based on the fixed point principle and splitting of the coefficient matrix with three extra parameters. The convergence of these procedures is also presented using some theorems. The validity of our methodologies is demonstrated via numerical examples.